Laju Dekomposisi Serasah Daun di Ekosistem Bakau Pulau Kelong, Kabupaten Bintan - I Wayan E.Dharmawan; Neviaty P. Zamani; Hawis H. Madduppa (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Decomposition Rate of Leaf Litter in The Mangrove Ecosystem of Kelong Island, Bintan Regency. The mangrove forests in the southeastern part of Kelong Island have abundant carbon reserves that indicate high primary productivity areas. Decomposition of leaf litter, as a part of regional productivity, produces simple essential nutrients utilized to sustain the growth of mangroves. The purpose of this study was to determine the decomposition rate of leaf litter in each zone of the study, the Landward (L), Middlezone (M), and Seaward (S) which is distinguished by the abundance of plant species and in situ environmental parameters. The experiment was conducted in March–May 2015 in the mangrove areas of Island Kelong, Bintan regency. The decomposition process was observed at six time intervals, i.e. 2, 4, 7, 14, 28, and 42 days using net bag containing 10 g of wet leaves placed on the substrate surface. The results showed that L was a zone with highest percentage of decomposition (56.34 ± 20.58%) compared to the M and S, respectively for 51.59 ± 15.46% and 51.09 ± 8.70%. The highest rate of litter decomposition in zone L was 1.40 ± 0.82 g·m-2·day-1 that was significantly different from the zones M and S, respectively of 0.83 ± 0.89 g·m-2·day-1 and 0.78 ± 0.70 g·m-2·day-1. Analysis of the coefficient of decomposition rate (k) indicated that the rate of decomposition in this region was high (k > 0.01). The decomposition rate has a significant correlation with the abundance of mangrove species, the salinity value of the water, and soil temperature.